PENGEMBANGAN MEDIA PEMBELAJARAN SCRAPBOOK PADA PEMBELAJARAN BAHASA INDONESIA KELAS IV SDN 107407 RIMOMUNGKUR (Jurnal Inovasi Sekolah Dasar, 2024)
The type of research used is research and development or Reseach and Development (R&D) using the ADDIE model which has five stages, namely the first stage of analysis (analysis), the design stage (design), the third stage of development (development), the fourth stage of implementation (implementation), and the fifth stage of evaluation (evaluation). The subjects in this study were fourth grade students of SDN 107407 Rimomungkur. The instruments used in data collection are observation, interview, material validation questionnaire, media validation questionnaire, education practicality questionnaire and test questions. The results of research on the development of Scrapbook learning media in Indonesian language learning class IV SDN 107407 Rimomungkur, on material validation obtained a score of 53 with a percentage value of 96.3% in the "Very Valid" category while media experts obtained a score of 74 with a percentage value of 98.6% in the "Very Valid" category so that the media is suitable for use in the learning process. In the practicality test obtained from the teacher's response through the questionnaire given, it got a score of 58 with a percentage value of 96.6% in the "Very Practical" category. and based on the effectiveness test obtained before using Scrapbook learning media obtained an average value of 29.3% in the "ineffective" category and after using Scrapbook learning media the average value obtained by students increased to 74.1% in the "effective" category and the scores obtained by students above the KKM between 70-90 after using Scrapbook learning media. Keywords: Development, Media, Learning, Scrapbook, Language